Investigation assistant with suspect anticipating intelligence - Abdullah, Saqueeb; Nibir, Farah Idid; Salam, Suraiya; Dey, Akash (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.